Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1021/jp2060602
|View full text |Cite
|
Sign up to set email alerts
|

Dopant Modulated Li Insertion in Si for Battery Anodes: Theory and Experiment

Abstract: Lithium-ion batteries are energy storage devices for portable electronics and are also of interest for more demanding applications, such as transportation. Present day Li-ion batteries feature a transition metal oxide cathode such as LiCoO 2 , LiMn 2 O 4 , or LiFePO 4 and a graphitic carbon anode. 1,2 These anode and cathode materials have Li capacities that are much less than desired. On the anode side, the graphitic anode presently utilized exhibits a low theoretical specific capacity of 372 mAhg À1 . 3 Othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 48 publications
9
107
0
Order By: Relevance
“…The cathodic current related to Li insertion for p-type Si increases at ~0.3 V indicating that it is forming the Li2.33Si phase [62], while the single anodic peak at ~0.5 V corresponds to the deformation of this Li2.33Si phase [63]. For the n-type Si, cathodic current does not increase until ~0.1 V, but it increases dramatically, forming a high Li mole fraction Li-Si phase in a narrow insertion potential window.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cathodic current related to Li insertion for p-type Si increases at ~0.3 V indicating that it is forming the Li2.33Si phase [62], while the single anodic peak at ~0.5 V corresponds to the deformation of this Li2.33Si phase [63]. For the n-type Si, cathodic current does not increase until ~0.1 V, but it increases dramatically, forming a high Li mole fraction Li-Si phase in a narrow insertion potential window.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effective carrier concentration at the interface between the Si(100) and 1 mol dm -3 (100) versus (111) for instance) is known to have negligible effect on the chemical potential for Li insertion into Si [63].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long et al [195] showed the effects of boron (B) and phosphorus (P) dopants on the lithiation of crystalline Si. By using Raman scattering spectroscopy, they were able to identify differences in Li insertion potentials for the different dopant types.…”
Section: The Influence Of Doping and Conductivity On The Performance mentioning
confidence: 99%
“…Long et al [68] measured the intensity of the characteristic phonon mode corresponding to crystalline silicon as a function of the electrode potential vs a Li/Li þ reference electrode. Since a decrease in the phonon mode intensity is indicative of the transition from crystalline to amorphous silicon, it corresponds to the onset of the lithiation process.…”
Section: Raman Spectroscopymentioning
confidence: 99%